(untitled) (Research, Society and Development, 2022)
The present study investigated the factors associated with the negative impact of the COVID19 pandemic on the sexual lives of the Brazilian population. A cross-sectional study was conducted with the adult, sexually active Brazilian population using an online survey. 807 adults completed questionnaires on socioeconomic information, sexual life, emotional aspects, and sleep aspects during the period of social withdrawal. The perception of a satisfactory sex life decreased by more than 20% during the pandemic compared to before the quarantine in addition to which 73.4% of people experience0d pain or discomfort during or after intercourse. Sleep-related aspects also had a negative impact on sexual life where 79.1% had changes in sleep pattern and difficulty falling asleep or waking up during the night with difficulty going back to sleep represented risk factors for having an affected sex life. The perception of the sexual life of Brazilian individuals was affected by social distancing during the pandemic of COVID-19.